Roles and responsibilities of libraries in increasing consumer health literacy and reducing health disparities - Jean, Beth St; Jindal, Gagan; Liao, Yuting; Jaeger, Paul T. (Advances in librarianship ;, 2020)
The rampant health injustices that occur daily throughout the world are exacerbated by health information injustice something which libraries and librarians play an instrumental role in addressing. This volume brings together librarians, LIS students, educators, and researchers, to discuss the many ways that information professionals and libraries serve as agents of securing health information justice. Kicking off with an introductory chapter which covers the central concepts of health information injustice, the following chapters focus on the roles of libraries and librarians in improving consumer health literacy and reducing health disparities in their communities. In the final chapter, the editors draw on the authors' work to highlight the ways in which libraries and librarians are moving us closer to health justice, and they also discuss how the COVID-19 pandemic is both illuminating and intensifying health disparities, reinforcing the need for libraries and librarians to continue their important roles as agents of health information justice to ensure the physical and intellectual accessibility of information for all.